Studies on the Suitability of Different Mould Media Compositions for the Mycological Evaluation of Hay Samples - Sipiczki, Bojána (Acta Agraria Debreceniensis, 2003)
t evaluating mould contamination of hay samples in more than the half of the cases Mucor spp. (and Trichoderma spp. in a smaller extent) overgrew slower developing moulds, spoiling the assessment of total mould CFU and the detection of fastidious organisms, among others the toxinogenic Fusaria. In parallel microbiological evaluation of hay samples comparing to the ISO 7954 medium as reference a) the overgrowth inhibiting effect of Rose Bengal (ISO 7954-RB); b) the combined inhibiting effect of Rose Bengal and Dichloran (dichloro-mononitroaniline) in DRBC; c) the inhibition of Dichlorane in ISO 7954 (ISO 7954-DC); d) the lowering of nutrient levels to 1/4 (1/4 N ISO 7954, 1/4 N-DRBC and 1/4 N-DC); e) the inhibiting effect of dinitro – salicylic – acid (DSA), a reducing sugar binding compound, as a potential growth inhibitor (RBC-DSA) were studied. The results showed, that 1) MSZ-ISO 7954 medium codified by the official method was unsuitable for the detemination of mould count and for the detection of toxinogic spp. in hay samples. In half of the cases the overgrowth of Mucor has spoiled CFU enumeration and recognition of toxinogenic moulds; 2) Inhibitor supplemented DRBC medium (King et al., 1979) enabled early CFU enumeration by uniforming colony sizes and by efficient suppression of Mucor, but the pink background colour of the medium was disturbing the observation of tints of conidia, which were characteristical to toxinogenic moulds like Fusaria. The hypha-staining property of Rose Bengal did not prove very important; 3) According to the recent stage of our studies, the ISO 7954-Dichloran combination can be recommended for the mycological evaluation of hays and dried roughages. CFU can be enumerated early, Mucor suppressed in the same extent as with DRBC and colours are easily observable; 4) 2-4-Dinitrosalicylic-acid (DSA) proved unsuitable as inhibitor, for its poor efficiency and for its intense yellow background coulour.